2009
DOI: 10.1007/s00276-009-0587-7
|View full text |Cite
|
Sign up to set email alerts
|

Variable patterns of cutaneous innervation on the dorsum of foot in fetuses

Abstract: A comparison with cutaneous innervation patterns found in other population groups revealed three new variants which have not been reported in the other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
2
16
0
2
Order By: Relevance
“…The nerves over the dorsum of foot also influence surgical incisions and the designing of neurovascular free flaps in this region. [1]…”
Section: Discussionmentioning
confidence: 99%
“…The nerves over the dorsum of foot also influence surgical incisions and the designing of neurovascular free flaps in this region. [1]…”
Section: Discussionmentioning
confidence: 99%
“…Literature analysis shows that previous researchers focused mainly on its anatomical variations [1,5,9,[14][15][16][17][18]. A limited number of studies concentrated on the histological analysis of the sural nerve [3,7,8,13].…”
Section: Discussionmentioning
confidence: 99%
“…Wahee et al were carried out on 60 lower limbs of 19 male and 11 female fetuses ranging between 24 and 36 weeks of gestation. Their results were divided into six groups, 5% Type1c and 3% Type3b which corresponded to K1 and K3 in Kosinski's classification (20). Based on their work on 30 adult cadavers, Aktan and Ucerler reported that the variation in the distribution of the cutaneous nerve of the dorsum of the foot could be classified into seven types.…”
Section: Resultsmentioning
confidence: 99%